Taurine Chloramine decreases cell viability and cytokine production in blood and spleen lymphocytes from septic rats - DALL’IGNA,DHÉBORA M. (2020)
Abstract Taurine (Tau) is an abundant amino acid in polymorphonuclear leukocytes that react with hypochlorous acid to form taurine chloramine (TauCl) under inflammatory conditions. We investigated potential interactions between lymphocytes and TauCl in rats submitted to cecal ligation. Animals were divided into sham or CLP groups (24 or 120 h) to isolate lymphocytes from blood and spleen. Lymphocytes were cultured at a concentration of 1×106 cells/mL and activated by concanavalin A. Tau and TauCl were added at 1, 10, and 100 μM. Cells were incubated with MTT to evaluate cell viability and cytokine concentration in the supernatant was determined. TauCl decreased lymphocyte viability and altered the secretion pattern of important inflammatory mediators in non-specific-phenotype manner. The effort to a is elucidate mechanisms of immune cell (dys)function in sepsis is important to better understand the complex regulation of immune system during sepsis development, and further studies are necessary to confirm TauCl as potential target in this context.